Lean Manufacturing Perceptions and Actual Practice Among Malaysian SME’s in Automotive Industry - A. N. M., Rose; B. M., Deros; M. N., Ab. Rahman (Universiti Malaysia Pahang, 2013)
Stiff business challenges and product competition faced by automotive component manufacturers has forced them to look into lean manufacturing (LM). Presently there are more than 100 LM practices. However, small and medium enterprises (SMEs) are not able to implement all LM practices due to financial, expertise and skill constraints. Therefore, in this study the authors investigated the level of perception and actual practice within 24 LM practices, regarding actions believed feasible to be implemented in SMEs. In addition, the authors gathered LM information sources, reasons for implementing LM and its benefits to SMEs. A questionnaire survey was conducted in 35 SMEs involves in manufacturing automotive components. The majority of SMEs have a high perception of the importance of LM practices but in reality are not undertaking them. The SMEs mainly received their LM information from their customers, and they strongly believe that LM practices could improve their long-term business sustainability and competitiveness in the market place.